2012
DOI: 10.1111/jbi.12035
|View full text |Cite
|
Sign up to set email alerts
|

Deep barriers, shallow divergences: reduced phylogeographical structure in the collared pika (Mammalia:Lagomorpha:Ochotona collaris)

Abstract: Aim Pikas (Ochotona spp.) are alpine specialists that show considerable morphological and genetic variation structured along latitudinal and elevational gradients. Recent studies of North American and Asian pikas have uncovered phylogeographical partitioning among separate mountain ranges and drainages, driven by Quaternary climate fluctuations. We tested the prediction that collared pikas (O. collaris) exhibit lower genetic diversity and less structure than other species of pika due to lower long‐term habitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 71 publications
3
27
0
Order By: Relevance
“…It seems that there is not a major discontinuity between populations of Afghan Pika based on cyt-b mitochondrial gene. This result is in agreement with those of populations of collared Pikas that are less geographically structured and their haplotypes more closely related to one another (Lanier & Olson, 2012).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It seems that there is not a major discontinuity between populations of Afghan Pika based on cyt-b mitochondrial gene. This result is in agreement with those of populations of collared Pikas that are less geographically structured and their haplotypes more closely related to one another (Lanier & Olson, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…The result of Fu's F s analysis for the Salouk population is in agreement with negative and significant value of Fu's F s , high haplotype and low nucleotide diversity in four populations of the rare species Ochotona koslowi in a small area of eastern China (Lin, Ci, Thirgood, Zhang, & Su, 2010). The two other species of Pikas, Ochotona collaris (Lanier & Olson, 2012) and Ochotona curzoniae (Ci et al, 2009), showed the same result of expansion based on negative value of Fu's F s test, high haplotype diversity and low nucleotide diversity in most of the populations.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Samples of 58 Collared Pikas from nine populations were collected, and their DNA was extracted as described previously (Lanier & Olson ; Table S1, Supporting information). Localities were chosen to broadly represent the species' range (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of historical biogeography of Collared Pikas have concluded that population differentiation has been in part driven by Pleistocene population distributions (Lanier & Olson ). Two mitochondrial lineages are present, corresponding to inferred western (Beringian) and eastern Pleistocene refugia (Lanier & Olson ). Studies of mountain goats (Shafer et al .…”
Section: Introductionmentioning
confidence: 99%